2018
DOI: 10.1108/ijhma-04-2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

Park proximity, crime and apartment prices

Abstract: Parks and open green spaces are an important part of the city landscape. Although studies show that proximity to parks and open green spaces has a mostly positive impact on house prices, several studies also report that crime in parks can affect buyers' perceptions, making nearby properties less desirable. We examine the effects of park proximity and crime in parks on apartment prices by using geographic information systems and hedonic modelling. Our results indicate that grass parks and park blocks are more d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Several studies have shown the positive impact of parks and public spaces on human health and well-being [16] while, others have shown that such places can be a reason for stress and anxiety [5,17] and affect human life negatively. According to Iqbal and Wilhelmsson [11], not all parks and public spaces have equal amenity value and some may be valued as disamenities. For example, noise around parks, high beam lights from sports arenas, and traffic congestion around parks, street parking near parks, garbage, vandalism, and the gathering of undesirable groups (such as alcoholics, drug addicts, etc.)…”
Section: Fear Of Crime and Perceived Safety In Public Spacesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown the positive impact of parks and public spaces on human health and well-being [16] while, others have shown that such places can be a reason for stress and anxiety [5,17] and affect human life negatively. According to Iqbal and Wilhelmsson [11], not all parks and public spaces have equal amenity value and some may be valued as disamenities. For example, noise around parks, high beam lights from sports arenas, and traffic congestion around parks, street parking near parks, garbage, vandalism, and the gathering of undesirable groups (such as alcoholics, drug addicts, etc.)…”
Section: Fear Of Crime and Perceived Safety In Public Spacesmentioning
confidence: 99%
“…in public spaces affect individuals negatively [8]. Poor maintenance and criminogenic conditions of the park and public spaces are highlighted by several researchers [9,11,18]. A small number of studies have also shown that potential buyers may avoid buying properties located near parks and public spaces with high crime rates [10,11,19].…”
Section: Fear Of Crime and Perceived Safety In Public Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Atmosphere 2020, 11, 152 7 of 20 Trees canopy can be perceived as aesthetically pleasing and valued from an environmental perspective as they decrease pollution levels [6]; however, at the same time, leaf fall can cause annoyance and decrease the sense of safety. Proximity to parks can be also considered as a negative factor, especially if it is considered an unsafe area [49].…”
Section: Supply Of Green Products and Servicesmentioning
confidence: 99%